The Effect of Microbial Fertilizers on Technological Characteristics of Some Cowpea (Vigna unguiculuta L. Walp.) Cultivars - Hamdi Özaktan; Ekrem Aktaş; Oğuz Erol; Melike İncetekin (Turkish Journal of Agriculture: Food Science and Technology, 2025)
Cowpea (Vigna unguiculata L. Walp.) is an annual herbaceous plant in the Fabaceae family. It is an important legume plant with 20-25% protein, 1.3-1.5% fat and 5.1-5.8% fiber, and has an important place in human and animal nutrition. In recent years, the rapid increase in the world population, the zoning of agricultural areas and the excessive use of chemical fertilizers in order to obtain higher yields from the unit area cause deterioration of the soil structure. Different methods have started to be applied to improve soil structure. One of these methods is the use of microbial fertilizers. Microbial fertilizers are an innovative and sustainable approach that improves chemical, physical and microbiological properties of soil and facilitates the uptake of plant nutrients. In this study, it was aimed to determine the effect of different microbial fertilizer applications on the technological characteristics of Akkız 86 and Karagöz 86 cowpea varieties by multivariate analysis methods. The minimum and maximum values obtained in the study are as follows: dry weight 17.98 - 19.29 g, dry volume 18.16 - 20.66 ml, fresh weight 42.15 - 46.53 g, fresh volume 44.16 - 47.83 ml, water absorption capacity 0.24 - 0.27 g/piece, water absorption index 1.33 - 1.66%, hydration coefficient 132.80 - 142. 55%, swelling capacity 0.256 - 0.296 ml/grain, swelling index 2.25 - 2.63%, unit volume weight 0.93 - 0.99 g/ml, cooking time 18.16 - 20.16 min and number of grains dispersed after cooking 0.33 - 2.66. In this study, İmed microbial fertilizer applied to cowpea plant had positive effects on cooking time, water absorption index, swelling index and swelling capacity parameters.